Léon Metchnikoff and the building of a geographical evolutionary model: the great historical rivers: os grandes rios históricos - Pedrosa, Breno Viotto (Geografares, 2021)
This article, which takes a contextual approach as a method, analyzes the book La Civilisation et les grands fleuves historiques written by the anarchist geographer Léon Metchnikoff, which proposes a geographical and historical model of interpretation for the human evolution. Based on clear theoretical assumptions, many of which are common to É. Reclus and P. Kropotkin, Metchnikoff divides his interpretive model into three major evolutionary stages. The analysis aims to elucidate his methodological statements, as well as the three stages of his theory. This study is justified by the impact of Civilisation on the human sciences, its fraternal nature and to question the interpretations that reaffirm geography as an eminently empirical science. As a result, one can identify the development of a geography capable to problematizing common senses of the time, notably European views on the East.
Keywords: Geography; Anarchism; Léon Metchnikoff; Geographical Theory